Extended tests for evaluating post-traumatic brain injury deficits in resource-limited settings: methods and pilot study data - Semework, Mulugeta; Laeke, Tsegazeab; Aklilu, Abenezer Tirsit; Tadele, Abraham; Ashagre, Yordanos; Teklewold, Peter; Kolias, Angelos G.; Hutchinson, Peter; Balcha, Abel; Yohannes, Dagnachew; Hassen, Getaw Worku (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI) is the leading cause of all injury-related deaths and disabilities within low to middle-income countries (LMICs). 1 Compared to high-income countries (HICs) individuals within LMICs experience nearly three times as many cases of TBI, a greater degree of the injuries resulting in disability, and are over twice as likely of dying following severe TBI. 1,2 Moreover, LMICs suffer from lower levels of funding for all levels of the health care system for patients suffering from TBI, causing those patients to return to the workforce before they are fully rehabilitated. These patients do not generally get comprehensive diagnostic workup, monitoring, or treatment, and return to work too quickly, often with undiagnosed post-traumatic deficits which in turn can lead to subsequent incidents of physical harm.Here, we share methods and results from our research project to establish innovative, simple, and scientifically based practices that dramatically leverage technology and validated testing strategies to identify post-TBI deficits quickly and accurately, to circumvent economic realities on the ground in LMICs.This study includes neurophysiological methods that can: 1) be implemented in LMICs and 2) test impairments caused by TBI, which generally affect brain processing speed, memory, and both executive and cognitive controls. We utilized paper tests such as the Montreal cognitive assessment (MoCA), line-bisection, and Bell's test.Furthermore, we combined modifications of neuroscience computer tasks to aid in assessing peripheral vision, memory, and analytical accuracies. Data from seventy-one subjects (51 patients and 20 controls, 15 females and 56 males) from 4 hospitals in Ethiopia are presented. The traumatic brain injury group consists of 17 mild, 28 moderate, and 8 severe patients (based on the initial Glasgow Comma Score). Controls are age and education-matched subjects (no known history of TBI, brain lesions, or spatial neglect symptoms).The main findings indicate that these examinations can identify several deficits, especially the MoCA test. These tests show great promise to assist in the evaluation of